Maintenance Versus Transmission Deficits: The Effect of Delay on Naming Performance in Aphasia - Martin, Nadine; Dell, Gary S. (Frontiers in Human Neuroscience, 2019)
We propose that deficits in lexical retrieval can involve difficulty in transmission of activation between processing levels, or difficulty in maintaining activation. In support, we present an investigation of picture naming by persons with aphasia in which the naming response is generated after a 1 second (sec) cue to respond in one condition or a 5 sec cue to respond in another. Some individuals did better after 5 secs, some did worse after 5 secs, and some were not impacted by the delay. It is suggested that better performance after 5 secs indicates a transmission deficit and that worse performance after 5 sec indicates a maintenance deficit. To support this hypothesis, we adapted the two-step semantic-phonological model of lexical retrieval (Schwartz et al., 2006) so that it can simulate the passage of time and can simulate lesions in transmission (its semantic and phonological connection strength parameters) and/or maintenance (its decay parameter). The naming error patterns after 1 and 5 secs for each participant were successfully fit to the model. Persons who did better after 5 secs were found to have low connection strength parameters, persons who did worse after 5 secs were simulated with an increased decay rate, and persons whose performance did not differ with delay were found to have lesions of both types. Some potential theoretical and clinical implications are discussed.